2017
DOI: 10.1126/sciadv.1700585
|View full text |Cite
|
Sign up to set email alerts
|

Carryover effects of larval exposure to different environmental bacteria drive adult trait variation in a mosquito vector

Abstract: The adult phenotype of mosquitoes depends on the types of bacteria encountered environmentally during development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
228
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(271 citation statements)
references
References 70 publications
18
228
2
5
Order By: Relevance
“…First, experimental studies show that mosquito larvae hatch with no extracellular microbes in their gut [13]. Second, studies of gut community composition indicate that most microbes identified in larvae overlap with the community of microbes that are present in their aquatic habitat [1318]. Third, mosquitoes host highly variable gut communities [1318], which would not be expected if these communities were acquired directly from parents or congeners.…”
Section: Acquisition Of a Gut Microbiota By Mosquito Larvaementioning
confidence: 99%
See 4 more Smart Citations
“…First, experimental studies show that mosquito larvae hatch with no extracellular microbes in their gut [13]. Second, studies of gut community composition indicate that most microbes identified in larvae overlap with the community of microbes that are present in their aquatic habitat [1318]. Third, mosquitoes host highly variable gut communities [1318], which would not be expected if these communities were acquired directly from parents or congeners.…”
Section: Acquisition Of a Gut Microbiota By Mosquito Larvaementioning
confidence: 99%
“…Second, studies of gut community composition indicate that most microbes identified in larvae overlap with the community of microbes that are present in their aquatic habitat [1318]. Third, mosquitoes host highly variable gut communities [1318], which would not be expected if these communities were acquired directly from parents or congeners. Exceptions to environmental acquisition are results showing that several types of bacteria are present in the reproductive tracts of adult mosquitoes, and that some of these bacteria are on the surface of eggs females lay [13, 15, 19–25].…”
Section: Acquisition Of a Gut Microbiota By Mosquito Larvaementioning
confidence: 99%
See 3 more Smart Citations